The kisspeptin-GnRH pathway in human reproductive health and disease - Skorupskaite, Karolina (Oxford University Press, 2014)
BACKGROUND: The discovery of kisspeptin as key central regulator of GnRH secretion has led to a new level of understanding of the neuroendocrine regulation of human reproduction. The related discovery of the kisspeptin-neurokinin B-dynorphin (KNDy) pathway in the last decade has further strengthened our understanding of the modulation of GnRH secretion by endocrine, metabolic and environmental inputs. In this review, we summarize current understanding of the physiological roles of these novel neuropeptides, and discuss the clinical relevance of these discoveries and their potential translational applications. METHODS: A systematic literature search was performed using PUBMED for all English language articles up to January 2014. In addition, the reference lists of all relevant original research articles and reviews were examined. This review focuses mainly on published human studies but also draws on relevant animal data. RESULTS: Kisspeptin is a principal regulator of the secretion of gonadotrophins, and through this key role it is critical for the onset of puberty, the regulation of sex steroid-mediated feedback and the control of adult fertility. Although there is some sexual dimorphism, both neuroanatomically and functionally, these functions are apparent in both men and women. Kisspeptin acts upstream of GnRH and, following paracrine stimulatory and inhibitory inputs from neurokinin B and dynorphin (KNDy neuropeptides), signals directly to GnRH neurones to control pulsatile GnRH release. When administered to humans in different isoforms, routes and doses, kisspeptin robustly stimulates LH secretion and LH pulse frequency. Manipulation of the KNDy system is currently the focus of translational research with the possibility of future clinical application to regulate LH pulsatility, increasing gonadal sex steroid secretion in reproductive disorders characterized by decreased LH pulsatility, including hypothalamic amenorrhoea and hypogonadotropic hypogonadism. Conversely there may be scope to reduce the activity of the KNDy system to reduce LH secretion where hypersecretion of LH adds to the phenotype, such as in polycystic ovary syndrome. CONCLUSIONS: Kisspeptin is a recently discovered neuromodulator that controls GnRH secretion mediating endocrine and metabolic inputs to the regulation of human reproduction. Manipulation of kisspeptin signalling has the potential for novel therapies in patients with pathologically low or high LH pulsatility.